Mastigodiaptomus galapagoensis n. sp. (Crustacea: Copepoda: Diaptomidae), a possibly extinct copepod from a crater lake of the Galápagos archipelago - Manuel Elías-Gutiérrez; Miriam Steinitz-Kannan; Eduardo Suárez-Morales; Carlos López (PeerJ, 2023)
Background A new species of a Neotropical diaptomid copepod is described based on individuals recovered from a small, almost forgotten collection of unique plankton samples from El Junco, a crater lake in San Cristóbal island, Galápagos archipelago. This copepod was regularly reported (1966–2004) as an abundant zooplankter in the lake, but it was not found in subsequent plankton surveys (2007–2018), and its specific identity remained unknown. In 2020, it was declared extinct because of introduced fish predation, rotenone treatment, and other major disturbances. The taxonomic examination of these invaluable specimens allowed us to recognize them as representing an undescribed species of the freshwater diaptomid genus Mastigodiaptomus Light, 1939. Methods Here, we describe the new species from El Junco crater lake, located in the San Cristóbal island a part of the Galápagos archipelago, collected with plankton nets. The description is based on detailed morphology, based on SEM and light microscopy. Results The taxonomic examination of these invaluable specimens allowed us to recognize them as representing an undescribed species of the freshwater diaptomid genus Mastigodiaptomus Light, 1939. The new species was readily assigned to this genus and is distinguished from its known congeners by details of (1) the male right fifth leg terminal claw and aculeus, (2) spiniform processes pattern of the right geniculate antennule segments 10–16, (3) length and structure of the spiniform process of the antepenultimate segment of the male right antennule, and (4) details of the dorsal process on the female fourth pediger. This finding represents the first report of this Neotropical copepod genus outside its original biogeographic region, the third species of a diaptomid copepod reported from insular freshwater systems, the southernmost record of Mastigodiaptomus, and the only freshwater calanoid in the Galápagos. The intriguing presence of this chiefly Neotropical copepod genus here could be related either to (1) human agency linked to pirate activities, commercial travelling by Spaniard ships, whaling activities, and intense tortoise hunting in San Cristóbal island. In the past, El Junco was the only freshwater source 600 nautical miles around, or (2) zoochory of resistant dormant stages passively transported by more than 65 migrating bird species known to settle in San Cristóbal. These two hypotheses cannot be properly tested at this time, so the explanation of the presence of this copepod will remain as a new open question in the fascinating natural history of the Galápagos.